Reproductive outcomes of cesarean scar pregnancies treated with uterine artery embolization combined with curettage - Yi-Ting Chen; Yu-Ching Chen; Ming Chen; Yu-Jun Chang; Shiao-Hsuan Yang; Horng-Der Tsai; Cheng-Hsuan Wu (Elsevier, 2022)
Objective: The aim of this study was to review the reproductive outcomes of women with a cesarean scar pregnancy (CSP) treated with dilation and curettage (D&C) after uterine artery embolization (UAE). Materials and methods: This was a retrospective study to review women who received UAE followed by D&C for CSP between January 2010 and December 2019 at the Changhua Christian Hospital, Changhua in Taiwan. Data were collected from both electronic and paper medical records. Patients were contact via phone call to follow up reproductive outcomes between January 2021 and March 2021. These subsequent reproductive outcomes (including pregnancy rate, secondary infertility rate, miscarriage rate, live birth rate, and recurrent CSP rate) were recorded and analyzed. Results: A total of 53 cases of women who received UAE followed by D&C for CSP were identified. The women's average age was 34.8 ± 5.1 years. The mean gestational age at diagnosis was 6.2 ± 1.1 weeks. The mean level for human chorionic gonadotropin was 23,407.7 ± 29,105.5 mIU/ml. The average of blood loss during D&C was 19.2 ± 43.6 ml. The average hospitalization time after D&C was 3.5 ± 1.1 days. Of the 53 cases, 10 patients were lost to follow-up and 43 patients agreed to follow-up on reproductive outcomes in 2021. Twenty-three patients who desired to conceive were analyzed. Nineteen out of these 23 women (82.6%) succeeded in conceiving again and gave birth to 15 healthy babies (78.9%). Only one woman (1/19, 5.3%) experienced recurrence of CSP. The average time interval between previous CSP treatment and subsequent conception was 10.4 ± 6.7 months. Conclusion: UAE combined with curettage treatment in CSP patients results in a positive rate of subsequent pregnancy outcomes. This minimally invasive procedure may be considered as one of the treatment options for CSP, as it enables preservation of fertility after treatment.